Morphological and biological properties of platelet-rich fibrin membrane produced from different centrifugation protocols - Tangkhunchaisaeng, Sarisa; Pongpirul, Krit; Satitpitakul, Vannarut (Chulalongkorn Medical Journal, 2025)
Background: Platelet-rich fibrin (PRF) membrane is a promising tool for the treatment of corneal epithelial disease; however, a standardized production protocol remains to be established. Objective: This study aimed to evaluate the morphological and biological properties of PRF membrane produced using different centrifugation protocols. Methods: Four distinct low-speed centrifugation protocols (100 × g/5 min, 200 × g/5 min, 100 × g/10 min, and 200 × g/10 min) were established for PRF membrane production from blood obtained from three healthy volunteers. We assessed the fibrin and membrane dimensions, white blood cell and platelet concentrations, kinetic release of growth factors (TGF-b, PDGF-BB, VEGF, and IGF-1), and inflammatory cytokines (IL-6, IL-1, and TNF-a). Furthermore, in vitro degradation and bacterial contamination were examined. Results: High platelet concentrations were consistently achieved in the PRF membranes produced by the four centrifugation protocols; however, there were no significant differences between these groups. Moreover, distinct release patterns were observed for each growth factor and cytokine. The PRF fibrin matrix effectively released growth factors over a sustained period of 3–10 days. Notably, no bacterial contamination was detected in any of the PRF membranes produced by the protocols. Conclusion: Our findings definitively demonstrate that a low-speed centrifugation protocol can be employed to produce PRF membrane with high platelet concentrations that release growth factors over an extended period, thereby offering substantial therapeutic potential for ocular surface diseases.